Catalyst for selectively catalyzing degradation of resistant genes in water and preparation method of catalyst

Through the multi-walled carbon nanotube catalyst supported by cobalt tetroxide and molecularly imprinted polymer, the problem of poor resistance gene removal effect in existing water treatment processes is solved, efficient resistance gene degradation and avoid water pollution.

CN119281389APending Publication Date: 2025-01-10NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411400644.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing water treatment process has poor effect on removing resistant genes, and the degradation ability of sulfate free radicals in advanced oxidation technology has significantly decreased in practical applications.

Method used

Using multi-walled carbon nanotubes supported by cobalt tetroxide and molecularly imprinted polymers as catalysts, the catalytic activity is improved and the selective recognition ability of the adversarial gene is increased, thereby avoiding excessive use of persulfate to cause water bodies. contaminate and provide a reaction carrier for sulfate radicals.

Benefits of technology

It significantly improves the degradation efficiency of resistance genes, avoids water pollution, and achieves efficient degradation of resistance genes in complex water environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281389A_ABST
    Figure CN119281389A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for selectively catalyzing degradation of resistant genes in water and a preparation method of the catalyst. The catalyst is a multiwalled carbon nanotube loaded with cobaltosic oxide and a molecularly imprinted polymer. The molecularly imprinted polymer is used for identifying resistance genes. According to the present invention, the high catalytic activity is provided, the selection pertinence of the molecular imprinting on the resistance gene (ARGs) can be increased, the reaction carrier of the sulfate radical free radical and the e-ARGs is provided, the degradation can be enhanced, and the catalytic degradation efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a catalyst for selectively catalyzing the degradation of resistance genes in water and a preparation method thereof. Background Art

[0002] Excessive or improper use of antibiotics induces pathogenic bacteria to produce antibiotic resistance genes (ARGs), which can continuously spread resistance through horizontal gene transfer (HGT), posing a serious threat to public health and are considered a new type of environmental pollutant. In 2019, 4.95 million deaths worldwide were related to bacterial resistance. Current water treatment processes are not effective in removing resistance genes.

[0003] In the prior art, advanced oxidation technology processes provide for the production of highly oxidizing sulfate free radicals (SO4·-), which can attack and destroy the phosphodiester bonds in DNA molecules, thereby causing the breakage and inactivation of gene sequences, such as the persulfate advanced oxidation process; although this technology has shown effective degradation capabilities for ARGs on a laboratory scale, sulfate free radicals are not selective for the degradation of ARGs. In actual applications, sulfate free radicals will react with a variety of organic matter in water, such as proteins and humic acid, resulting in a significant decrease in the ability to degrade ARGs.

[0004] Therefore, for the degradation of ARGs in the actual environment, a well-targeted and highly selective additive is needed to assist the catalytic degradation process and improve the degradation rate of resistance genes in water. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a catalyst for selectively catalyzing the degradation of resistance genes in water and a preparation method thereof.

[0006] In the first aspect, the present invention provides a catalyst for selectively catalyzing the degradation of resistance genes in water, wherein the catalyst is a porous network three-dimensional structure, and the catalyst is a multi-walled carbon nanotube loaded with cobalt tetroxide and molecular imprinting polymer; the molecular imprinting polymer is used to selectively identify resistance genes from chemical pollutants in water bodies; the resistance genes are antibiotic resistance genes produced by pathogenic bacteria, and the resistance genes include tetracycline resistance genes, sulfonamide resistance genes, macrolide resistance genes, and lactam resistance genes.

[0007] Description: In the above method, cobalt tetroxide solid and molecular imprinting are used to load multi-walled carbon nanotubes, which can form a three-dimensional structure with the multi-walled carbon nanotubes during the loading process. The three-dimensional structure not only has higher catalytic activity, but also can increase the selectivity of molecular imprinting for e-ARGs, which can avoid new pollution to water bodies caused by excessive use of persulfate, and at the same time provide a reaction carrier for sulfate radicals and e-ARGs, thereby enhancing the degradation process and improving the efficiency of catalytic degradation.

[0008] In a second aspect, the present invention also provides a method for preparing a catalyst for selectively catalyzing the degradation of resistance genes in water, comprising:

[0009] S1. Using Co(NO3)2·6H2O as a cobalt source, the cobalt source is loaded onto multi-walled carbon nanotubes by a solvothermal method to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide; the cobalt tetroxide is in the form of nano-microspheres;

[0010] S2. Adding the multi-walled carbon nanotubes loaded with cobalt tetroxide to a prepolymer formed by a prepolymerization reaction using guanine as a template molecule and methacrylic acid as a functional monomer to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and the prepolymer, and then eluting the template molecules in the multi-walled carbon nanotubes loaded with cobalt tetroxide and the prepolymer to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and a molecular imprinting polymer.

[0011] Description: The above steps provide a method for preparing a porous network three-dimensional structure. The preparation method can combine cobalt tetroxide with multi-walled carbon nanotubes in the form of nano-microspheres, and utilize the high catalytic activity of nano-microsphere cobalt tetroxide and the high recognition effect of molecular imprinting polymers on resistance genes to produce a good catalytic effect on the degradation process.

[0012] Furthermore, before S1, the multi-walled carbon nanotubes are pretreated, and the pretreatment method is: performing enhanced carboxylation treatment and vinyl modification treatment on the multi-walled carbon nanotubes in sequence.

[0013] Description: Since the carboxyl content of general multi-walled carbon nanotubes is low (e.g. 0.7wt%), in order to increase the carboxyl content of multi-walled carbon nanotubes, thereby increasing the number of reactive sites in the subsequent molecular imprinting polymer synthesis process, so as to facilitate the polymerization reaction and obtain a better porous network structure, it is necessary to carry out a strengthened carboxylation reaction on the purchased multi-walled carbon nanotubes with low carboxyl content, thereby increasing the carboxyl content on the surface of the multi-walled carbon nanotubes. At the same time, the introduced carboxyl groups cannot directly provide reaction sites for the subsequent generation of molecular imprinting polymers, and the generated carboxyl groups may affect the subsequent loading of nano-cobalt tetroxide on the multi-walled carbon nanotubes, so it is necessary to introduce vinyl groups on the surface of carbon nanotubes through reaction with carboxyl groups to eliminate the influence on the loading of nano-cobalt tetroxide.

[0014] Furthermore, the enhanced carboxylation treatment of the multi-walled carbon nanotubes includes:

[0015] S01, taking equal masses of multi-walled carbon nanotubes and KNO3 and mixing them in a first container, adding water and dispersing them in a ratio of 100 mg of multi-walled carbon nanotubes to water in the range of 10 to 15 mL, and adding concentrated sulfuric acid and dispersing them in a ratio of 100 mg of multi-walled carbon nanotubes to concentrated sulfuric acid in the range of 40 to 50 mL;

[0016] S02, then add KMnO4 at a mass ratio of multi-walled carbon nanotubes to KMnO4 of 1:2, and place the first container in a 40-50°C water bath for ultrasonic treatment for 2-3h;

[0017] S03. Raise the water bath temperature to 60-70° C., then add 30% hydrogen peroxide solution at a ratio of 100 mg of multi-walled carbon nanotubes to 15-22 mL of hydrogen peroxide solution, stir and condense under reflux for 35-40 minutes, then lower the temperature to room temperature, add water 5-7 times the volume of the hydrogen peroxide solution to dilute, then filter and wash, complete the enhanced carboxylation treatment of the multi-walled carbon nanotubes, and obtain carboxylated carbon nanotubes.

[0018] Note: The above steps can obtain carboxylated multi-walled carbon nanotubes (MWCNT-COOH) after strengthening treatment.

[0019] Furthermore, the vinyl modification treatment of the multi-walled carbon nanotubes includes:

[0020] S04, in a second container, ultrasonically disperse the carboxylated carbon nanotubes obtained in S03 in SOCl2 liquid at a ratio of 100 mg: 25-30 mL for 25-35 min, then place the second container in a constant temperature water bath at 65-75° C., stir and condense and reflux for 22-26 h, centrifuge, and wash with tetrahydrofuran to obtain a dispersed product;

[0021] S05. In a third container, the dispersed product is placed in tetrahydrofuran at a ratio of 100 mg: 25-30 mL, and then 4-dimethylaminopyridine and 3-butene-1-ol are added in a ratio of 100 mg: 200-300 mg: 1-2 ml in sequence; then the third container is placed in a constant temperature water bath at 65-75°C, stirred and condensed under reflux for 22-26 hours, centrifuged, washed with tetrahydrofuran, and dried to obtain vinyl-modified multi-walled carbon nanotubes.

[0022] Note: The above steps can produce vinyl-modified multi-walled carbon nanotubes (MWCNT—CH=CH2).

[0023] Furthermore, the method of loading the cobalt source onto the surface of the multi-walled carbon nanotubes by a solvothermal method comprises:

[0024] In a fourth container, dissolve Co(NO3)2·6H2O in n-hexanol at a ratio of 10 mg:1 ml to form a cobalt solution;

[0025] The mass ratio of multi-walled carbon nanotubes to Co(NO3)2·6H2O is 1 mg:5 mg. The multi-walled carbon nanotubes are placed in a cobalt solution for ultrasonic dispersion for 1 to 3 hours, and then a fourth container is placed in an oil bath at 120 to 180°C, stirred for reaction and condensed under reflux for 8 to 12 hours, cooled to room temperature, and then centrifuged to obtain a black powder. After washing and drying, multi-walled carbon nanotubes loaded with nano-microspherical cobalt tetroxide are obtained.

[0026] Note: The above steps can obtain multi-walled carbon nanotubes loaded with nano-microspherical cobalt tetroxide.

[0027] Furthermore, the step of adding the multi-walled carbon nanotubes loaded with cobalt tetroxide to a prepolymer formed by a prepolymerization reaction using guanine as a template molecule and methacrylic acid as a functional monomer comprises:

[0028] 1) placing the cobalt oxide-loaded multi-walled carbon nanotubes prepared from 100 mg of the multi-walled carbon nanotubes in a fifth container, wherein the fifth container contains a mixed solvent formed by mixing 100 ml of acetonitrile and 20 ml of toluene;

[0029] 2) Add guanine solution and methacrylic acid into the fifth container, ultrasonicate the fifth container in a water bath at 30-40°C for 30-40 minutes, and then purge with nitrogen for 8-12 minutes;

[0030] The volume ratio of guanine solution to toluene is 1:1.1-1.5, the guanine solution is an N,N'-dimethylformamide solution with a concentration of 19-23 mol / L guanine, and the molar ratio of guanine to methacrylic acid is 1:5;

[0031] 3) Then, 6 mmol of a cross-linking agent and 100 mg of an initiator were added to the fifth container, and magnetic stirring was performed for 20 min under N2 conditions; then, the fifth container was placed in a constant temperature water bath at 65-75° C., stirred and condensed under reflux for 10-13 h, and centrifuged to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and guanine template molecular polymers.

[0032] Description: Through the above steps, multi-walled carbon nanotubes loaded with cobalt tetroxide and guanine template molecular polymers can be formed, and a three-dimensional structure is initially formed.

[0033] Furthermore, the elution of the guanine template molecule includes: sequentially using an eluent consisting of methanol and acetic acid and an HCl solution for elution, and eluting until the supernatant of the washing solution does not contain guanine, and the elution is completed.

[0034] Note: In order to form active sites with specific adsorption in molecularly imprinted polymers, the template molecules introduced during the polymerization process need to be eluted out of the polymer network to form the final catalyst with a porous network structure.

[0035] In a third aspect, the present invention also provides an application of a catalyst, wherein the catalyst is used in a degradation process of resistance genes in water, and the catalyst is used to catalyze the degradation process; the degradation process is a persulfate advanced oxidation degradation method.

[0036] Description: The above catalyst has a good promoting effect in the persulfate advanced oxidation degradation process.

[0037] The beneficial effects of the present invention are:

[0038] The present invention uses cobalt tetroxide solid and molecular imprinting to load multi-walled carbon nanotubes, which can form a three-dimensional structure with the multi-walled carbon nanotubes during the loading process. The three-dimensional structure not only has high catalytic activity, but also can increase the selectivity of molecular imprinting for e-ARGs, and can avoid new pollution to water bodies caused by excessive use of persulfate. At the same time, it provides a reaction carrier for sulfate radicals and e-ARGs, thereby strengthening the degradation process and improving the efficiency of catalytic degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of the reaction principle of the molecular imprinting polymer of the present invention;

[0040] Figure 2 is a SEM image of Example 1 of the present invention;

[0041] Figure 3The SEM (a) of Example 1 of the present invention and the C (b), O (c), and Co (d) element mapping diagrams of the region;

[0042] Figure 4 is a Fourier transform infrared spectrum (FT-IR) diagram of Example 1 of the present invention;

[0043] Figure 5 It is the data graph of the degradation removal rate (a) and kinetics (b) of Example 1 of the present invention and Comparative Example 1;

[0044] Figure 6 It is a data graph showing the effect of DNA concentration on removal efficiency (a) and kinetics (b) of the present invention;

[0045] Figure 7 is a data diagram of the effects of different concentrations of competitive pollutants on degradation in the present invention;

[0046] Figure 8 This is a recycling data diagram of the catalyst of Example 1 of the present invention;

[0047] Fig. 9 is the circular gene map of pET-29a(+) in the experimental example of the present invention;

[0048] Fig.10 It is the standard curve of the resistance gene copy number in the experimental example of the present invention. DETAILED DESCRIPTION

[0049] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0050] Example 1: A catalyst for selectively catalyzing the degradation of resistance genes in water, the catalyst having a porous network structure, and the catalyst being a multi-walled carbon nanotube loaded with cobalt tetroxide and a molecular imprinting polymer; the molecular imprinting polymer is used to selectively identify resistance genes from chemical pollutants in water; the resistance genes are antibiotic resistance genes produced by pathogenic bacteria, and illustratively, the resistance genes may include tetracycline resistance genes, sulfonamide resistance genes, macrolide resistance genes, and lactam resistance genes; the SEM image of the porous network structure is as follows Figure 2 As shown. The Fourier transform infrared spectrum (FT-IR) is shown Figure 4 shown.

[0051] The process of molecular imprinting technology is as follows Figure 1As shown, molecular imprinting technology achieves specific matching with target molecules by constructing a porous mesh three-dimensional structure, showing good application prospects in the process of pollutant identification and degradation. Therefore, in the embodiment of the present invention, molecular imprinting technology is combined with advanced oxidation technology to achieve efficient degradation of resistance genes in complex water environments.

[0052] The preparation method of the catalyst comprises S1-S2:

[0053] The multi-walled carbon nanotubes are pretreated, and the pretreatment method is: the multi-walled carbon nanotubes are sequentially subjected to enhanced carboxylation treatment and vinyl modification treatment.

[0054] Specifically, the enhanced carboxylation treatment of multi-walled carbon nanotubes includes S01-S03:

[0055] S01, taking equal masses of multi-walled carbon nanotubes and KNO3 and mixing them in a first container, adding water and dispersing them in a ratio of 100 mg of multi-walled carbon nanotubes to water in the range of 10 to 15 mL, and adding concentrated sulfuric acid and dispersing them in a ratio of 100 mg of multi-walled carbon nanotubes to concentrated sulfuric acid in the range of 40 to 50 mL;

[0056] S02, then add KMnO4 at a mass ratio of multi-walled carbon nanotubes to KMnO4 of 1:2, and place the first container in a 40-50°C water bath for ultrasonic treatment for 2-3h;

[0057] S03. Raise the water bath temperature to 60-70° C., then add 30% hydrogen peroxide solution at a ratio of 100 mg of multi-walled carbon nanotubes to 15-22 mL of hydrogen peroxide solution, stir and condense under reflux for 35-40 minutes, then lower the temperature to room temperature, add water 5-7 times the volume of the hydrogen peroxide solution to dilute, then filter and wash, complete the enhanced carboxylation treatment of the multi-walled carbon nanotubes, and obtain carboxylated carbon nanotubes.

[0058] For example, in Example 1, 100 mg of multi-walled carbon nanotubes (MWCNT) and 100 mg of KNO3 were placed in a 250 ml double-necked flask, and 13 ml of deionized water was added for ultrasonic dispersion; 47 ml of concentrated H2SO4 (98%) was slowly added under 0°C ice-water mixing bath conditions, and the MWCNT was evenly dispersed by magnetic stirring for 40 min; 200 mg of KMnO4, 40℃ water bath ultrasonic for 2h; raise the water bath temperature to 60℃, then slowly add 20mL of 30% hydrogen peroxide solution, reflux reaction for 40min; when the temperature drops to room temperature, add 120ml of deionized water to dilute the reaction system, use a Buchner funnel with a 0.45μm nylon filter membrane to separate the enhanced carboxylation multi-walled carbon nanotubes; prepare 5wt% dilute hydrochloric acid to wash the reaction product 2 to 3 times and filter and separate; use anhydrous ethanol to wash again until the washing solution is neutral pH=7, and fully dry at 80℃ to obtain enhanced carboxylation multi-walled carbon nanotubes (MWCNT-COOH).

[0059] Specifically, the vinyl modification treatment of the multi-walled carbon nanotubes includes S04-S05:

[0060] S04, in a second container, ultrasonically disperse the carboxylated carbon nanotubes obtained in S03 in SOCl2 liquid at a ratio of 100 mg: 25-30 mL for 25-35 min, then place the second container in a constant temperature water bath at 65-75° C., stir and condense and reflux for 22-26 h, centrifuge, and wash with tetrahydrofuran to obtain a dispersed product;

[0061] S05. In a third container, the dispersed product is placed in tetrahydrofuran at a ratio of 100 mg: 25-30 mL, and then 4-dimethylaminopyridine and 3-butene-1-ol are added in a ratio of 100 mg: 200-300 mg: 1-2 ml in sequence; then the third container is placed in a constant temperature water bath at 65-75°C, stirred and condensed under reflux for 22-26 hours, centrifuged, washed with tetrahydrofuran, and dried to obtain vinyl-modified multi-walled carbon nanotubes.

[0062] For example, in Example 1, (1) acyl halide of carboxyl group: the enhanced carboxylated carbon nanotubes were added to a 100 ml single-necked round-bottom flask, followed by adding 30 ml SOCl2 for ultrasonic dispersion for 30 min, and the reaction system was placed in a 70°C constant temperature water bath with stirring and reflux for 24 h. The product was separated by centrifugation, washed 3 to 4 times with tetrahydrofuran (THF), and no drying was required. (2) Introduction of vinyl group: the product obtained in the previous step was dispersed in 30 ml THF, 250 mg 4-DMAP and 1.721 ml 3-butene-1-ol were added, and the mixture was refluxed in a 60°C water bath with magnetic stirring for 24 h. The product was separated by centrifugation, washed 2 to 3 times with THF, and dried at 60°C to finally obtain vinyl-modified multi-walled carbon nanotubes (MWCNT—CH=CH2).

[0063] S1. Using Co(NO3)2·6H2O as a cobalt source, the cobalt source is loaded onto multi-walled carbon nanotubes by a solvothermal method to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide; the cobalt tetroxide is in the form of nano-microspheres;

[0064] Specifically, the method of loading the cobalt source onto the surface of the multi-walled carbon nanotubes by the solvothermal method includes:

[0065] In a fourth container, dissolve Co(NO3)2·6H2O in n-hexanol at a ratio of 10 mg:1 ml to form a cobalt solution;

[0066] The multi-walled carbon nanotubes are placed in a cobalt solution and ultrasonically dispersed for 1 to 3 hours, and then the fourth container is placed in an oil bath at 120 to 180° C., stirred for reaction and condensed under reflux for 8 to 12 hours, cooled to room temperature, and then centrifuged to obtain a black powder, which is washed and dried to obtain multi-walled carbon nanotubes loaded with nano-microspherical cobalt tetroxide.

[0067] Illustratively, in Example 1, 500 mg of Co(NO3)2·6H2O was dissolved in 50 ml of n-hexanol to form a red solution; then the modified multi-walled carbon nanotubes prepared in the previous step were dispersed in the red solution by ultrasound for 2 h; then the reaction system was placed in a 140°C oil bath reflux device and reacted with magnetic stirring for 10 h; after cooling to room temperature, the mixture was centrifuged and the generated black powder was washed 2 to 3 times with anhydrous ethanol, and dried at 80°C to obtain modified multi-walled carbon nanotubes loaded with nano-Co3O4 (Co3O4@MWCNT-C=C).

[0068]

[0069] S2. Adding the multi-walled carbon nanotubes loaded with cobalt tetroxide to a prepolymer formed by a prepolymerization reaction using guanine as a template molecule and methacrylic acid as a functional monomer to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and the prepolymer, and then eluting the template molecules in the multi-walled carbon nanotubes loaded with cobalt tetroxide and the prepolymer to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and a molecular imprinting polymer.

[0070] Specifically, adding the multi-walled carbon nanotubes loaded with cobalt tetroxide to a prepolymer formed by a prepolymerization reaction using guanine as a template molecule and methacrylic acid as a functional monomer comprises:

[0071] 1) placing the multi-walled carbon nanotubes loaded with cobalt tetroxide in a fifth container, wherein the fifth container contains a mixed solvent formed by mixing acetonitrile and toluene in a volume ratio of 5 to 6:1;

[0072] 2) Add the guanine solution and methacrylic acid into the fifth container, ultrasonicate the fifth container in a water bath at 30-40° C. for 30-40 min, and then purge with nitrogen for 8-12 min;

[0073] The volume ratio of guanine solution to toluene is 1:1.1-1.5, the guanine solution is an N,N'-dimethylformamide solution with a concentration of 19-23 mol / L guanine, and the molar ratio of guanine to methacrylic acid is 1:5;

[0074] 3) Then add a crosslinking agent and an initiator into the fifth container, and stir magnetically for 20 minutes under N2 conditions; then place the fifth container in a constant temperature water bath at 65-75°C, stir and reflux for 10-13 hours, and centrifuge to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and guanine template molecular polymers.

[0075] For example, in Example 1, (1) the material prepared in the previous step is added to a 250 ml double-necked round-bottom flask containing a mixed solvent of 100 ml of acetonitrile and 20 ml of toluene. (2) 0.5 mmol of guanine as a template molecule and 2.5 mmol of MAA as a functional monomer dissolved in 25 mL of N,N'-dimethylformamide (DMF) are added to the reaction flask, and water bath ultrasound is performed at 35°C for 30 min to promote the formation of intermolecular hydrogen bonds. After water bath ultrasound, nitrogen is purged for 10 min. (3) 6 mmol of crosslinker EGDMA and 100 mg of initiator AIBN are added to the reaction flask, and magnetic stirring is performed for 20 min under N2 conditions. After other gas impurities in the system are discharged, the reaction device is sealed. (4) The reaction is stirred and refluxed in a constant temperature water bath at 70°C for 12 h. After the reaction product is cooled, it is separated using a centrifuge at a speed of 5000 r / min to finally obtain a polymer containing a guanine template molecule.

[0076] Specifically, the elution of the guanine template molecule includes: sequentially eluting with an eluent consisting of methanol and acetic acid and an HCl solution, and eluting until the supernatant of the washing solution does not contain guanine, and the elution is completed.

[0077] For example, in Example 1, (1) an eluent having a volume ratio of methanol to acetic acid of 9:1 is prepared, 40 ml of the eluent is added to the template-containing material each time, and a vortex mixer is used for high-speed oscillation for 15 minutes, and a high-speed centrifuge is used for centrifugation at a speed of 5000 r / min for 5 minutes, and the elution is repeated 3 times. (2) a 1M HCl solution is prepared, and the material is washed and centrifuged according to the method in the previous step. (3) the hydrochloric acid, methanol and acetic acid residues are washed with anhydrous ethanol according to the method in (1), and the absorbance of the supernatant after centrifugation is measured at wavelengths of 274 nm and 244 nm using an ultraviolet spectrophotometer until no guanine residues are detected in the supernatant at these two wavelengths. After elution is completed, the material is placed in an oven at 60°C and dried for 12 hours.

[0078] Example 2: This example is different from Example 1 in that the parameters in the preparation process are different, specifically:

[0079] S01, taking equal masses of multi-walled carbon nanotubes and KNO3 and mixing them in a first container, and then adding water and dispersing them in a ratio of 100 mg:10 mL of multi-walled carbon nanotubes to water, and adding concentrated sulfuric acid and dispersing them in a ratio of 100 mg:40 mL of multi-walled carbon nanotubes to concentrated sulfuric acid;

[0080] S02, then add KMnO4 at a mass ratio of multi-walled carbon nanotubes to KMnO4 of 1:2, and place the first container in a 40°C water bath for ultrasonic treatment for 2h;

[0081] S03. Raise the water bath temperature to 60°C, then add 30% hydrogen peroxide solution at a ratio of 100 mg:15 mL of multi-walled carbon nanotubes to hydrogen peroxide solution, stir and condense under reflux for 35 minutes, then lower the temperature to room temperature, add water 5 times the volume of the hydrogen peroxide solution to dilute, then filter and wash, complete the enhanced carboxylation treatment of the multi-walled carbon nanotubes, and obtain carboxylated carbon nanotubes.

[0082] S04, in a second container, the carboxylated carbon nanotubes obtained in S03 were ultrasonically dispersed in SOCl2 liquid at a ratio of 100 mg: 25 mL for 25 min, and then the second container was placed in a constant temperature water bath at 65° C., stirred and condensed under reflux for 22 h, centrifuged, and washed with tetrahydrofuran to obtain a dispersed product;

[0083] S05. In a third container, the dispersed product is placed in tetrahydrofuran at a ratio of 100 mg:25 mL, and then 4-dimethylaminopyridine and 3-butene-1-ol are added in a ratio of 100 mg:200 mg:1 ml in sequence; then the third container is placed in a constant temperature water bath at 65°C, stirred and condensed under reflux for 22 hours, centrifuged, washed with tetrahydrofuran, and dried to obtain vinyl-modified multi-walled carbon nanotubes.

[0084] S1. Using Co(NO3)2·6H2O as a cobalt source, the cobalt source is loaded onto multi-walled carbon nanotubes by a solvothermal method to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide; the cobalt tetroxide is in the form of nano-microspheres;

[0085] In a fourth container, dissolve Co(NO3)2·6H2O in n-hexanol at a ratio of 10 mg:1 ml to form a cobalt solution;

[0086] The multi-walled carbon nanotubes were placed in a cobalt solution and ultrasonically dispersed for 1 hour, and then the fourth container was placed in a 120°C oil bath, stirred for reaction and condensed under reflux for 8 hours, cooled to room temperature, and then centrifuged to obtain a black powder, which was washed and dried to obtain multi-walled carbon nanotubes loaded with nano-microspherical cobalt tetroxide.

[0087] S2. Adding the multi-walled carbon nanotubes loaded with cobalt tetroxide to a polymerization reaction with guanine as a template molecule and methacrylic acid as a functional monomer to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and guanine template molecule polymers, and then eluting the guanine template molecules to obtain the multi-walled carbon nanotube catalyst with a porous network structure.

[0088] 1) placing the multi-walled carbon nanotubes loaded with cobalt tetroxide in a fifth container, wherein the fifth container contains a mixed solvent formed by mixing acetonitrile and toluene in a volume ratio of 5:1;

[0089] 2) Add the guanine solution and methacrylic acid into the fifth container, ultrasonicate the fifth container in a 30° C. water bath for 30 min, and then purge with nitrogen for 8 min;

[0090] The volume ratio of guanine solution to toluene is 1:1.1, the guanine solution is a 19 mol / L guanine solution in N,N'-dimethylformamide, and the molar ratio of guanine to methacrylic acid is 1:5;

[0091] 3) Then, a crosslinking agent and an initiator are added to the fifth container, and magnetic stirring is performed for 20 minutes under N2 conditions; then, the fifth container is placed in a constant temperature water bath at 65°C, stirred and condensed under reflux for 10 hours, and centrifuged to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and guanine template molecular polymers.

[0092] Example 3: This example is different from Example 1 in that the parameters in the preparation process are different, specifically:

[0093] S01, taking equal masses of multi-walled carbon nanotubes and KNO3 and mixing them in a first container, and then adding water and dispersing them in a ratio of 100 mg:15 mL of multi-walled carbon nanotubes to water, and adding concentrated sulfuric acid and dispersing them in a ratio of 100 mg:50 mL of multi-walled carbon nanotubes to concentrated sulfuric acid;

[0094] S02, then add KMnO4 at a mass ratio of multi-walled carbon nanotubes to KMnO4 of 1:2, and place the first container in a 50°C water bath for ultrasonic treatment for 3h;

[0095] S03. Raise the water bath temperature to 70°C, then add 30% hydrogen peroxide solution at a ratio of 100 mg:22 mL of multi-walled carbon nanotubes to hydrogen peroxide solution, stir and condense under reflux for 40 minutes, then lower the temperature to room temperature, add water 7 times the volume of the hydrogen peroxide solution to dilute, then filter and wash, complete the enhanced carboxylation treatment of the multi-walled carbon nanotubes, and obtain carboxylated carbon nanotubes.

[0096] S04, in a second container, the carboxylated carbon nanotubes obtained in S03 were ultrasonically dispersed in SOCl2 liquid at a ratio of 100 mg:30 mL for 35 min, and then the second container was placed in a constant temperature water bath at 75°C, stirred and condensed under reflux for 26 h, centrifuged, and washed with tetrahydrofuran to obtain a dispersed product;

[0097] S05. In a third container, the dispersed product is placed in tetrahydrofuran at a ratio of 100 mg:30 mL, and then 4-dimethylaminopyridine and 3-butene-1-ol are added in a ratio of 100 mg:300 mg:2 ml in sequence; then the third container is placed in a constant temperature water bath at 75°C, stirred and condensed under reflux for 26 hours, centrifuged, washed with tetrahydrofuran, and dried to obtain vinyl-modified multi-walled carbon nanotubes.

[0098] S1. Using Co(NO3)2·6H2O as a cobalt source, the cobalt source is loaded onto multi-walled carbon nanotubes by a solvothermal method to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide; the cobalt tetroxide is in the form of nano-microspheres;

[0099] In a fourth container, dissolve Co(NO3)2·6H2O in n-hexanol at a ratio of 10 mg:1 ml to form a cobalt solution;

[0100] The multi-walled carbon nanotubes were placed in a cobalt solution and ultrasonically dispersed for 3 hours, and then the fourth container was placed in an oil bath at 180°C, stirred for reaction and condensed under reflux for 12 hours, cooled to room temperature, and then centrifuged to obtain a black powder, which was washed and dried to obtain multi-walled carbon nanotubes loaded with nano-microspherical cobalt tetroxide.

[0101] S2. Adding the multi-walled carbon nanotubes loaded with cobalt tetroxide to a polymerization reaction with guanine as a template molecule and methacrylic acid as a functional monomer to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and guanine template molecule polymers, and then eluting the guanine template molecules to obtain the multi-walled carbon nanotube catalyst with a porous network structure.

[0102] 1) placing the multi-walled carbon nanotubes loaded with cobalt tetroxide in a fifth container, wherein the fifth container contains a mixed solvent formed by mixing acetonitrile and toluene in a volume ratio of 6:1;

[0103] 2) Add the guanine solution and methacrylic acid into the fifth container, ultrasonicate the fifth container in a water bath at 30-40° C. for 40 min, and then purge with nitrogen for 12 min;

[0104] The volume ratio of guanine solution to toluene is 1:1.5, the guanine solution is a 23 mol / L guanine solution in N,N'-dimethylformamide, and the molar ratio of guanine to methacrylic acid is 1:5;

[0105] 3) Then, a crosslinking agent and an initiator were added to the fifth container, and magnetic stirring was performed for 20 minutes under N2 conditions; then, the fifth container was placed in a 75° C. constant temperature water bath, stirred and condensed under reflux for 13 hours, and centrifuged to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and guanine template molecular polymers.

[0106] Comparative Example 1:

[0107] The multi-walled carbon nanotubes were not loaded with molecularly imprinted polymers.

[0108] Comparative Example 2:

[0109] The multi-walled carbon nanotubes were not subjected to enhanced carboxylation treatment or vinyl modification treatment.

[0110] Comparative Example 3:

[0111] The multi-walled carbon nanotubes were not subjected to vinyl modification.

[0112] Experimental example:

[0113] 1. Morphological characterization: Figure 2 As shown,

[0114] Figure 2(a, b) It can be seen that the molecular imprinted polymer uses carbon nanotubes as carriers and has an uneven structure, which provides a large specific adsorption site for the catalytic material. The location of the polymer is mainly concentrated at the end of the carbon nanotube. This is because the defects (such as vacancies, kinks and edge planes) in the carbon nanotube structure are the reaction sites for the formation of covalent carbon-oxygen bonds. In the carboxylation treatment step, the main reaction active site of the mixed acid oxidation step is at the end of the carbon nanotube with more defective structures, so the double bond structure involved in the polymerization process is more located at the end of the carbon nanotube.

[0115] Combination Figure 2 (d) Figure 2 (a) SEM image and Figure 3 (b, c, d) Single element mapping analysis of the three elements C, O, and Co shows that the Co3O4 nanoparticles and molecular imprinting polymers loaded during the material synthesis process are similar to the main loads on the ends of carbon nanotubes. The Co3O4 nanoparticles and molecular imprinting polymers are in a relatively uniform structure, which also helps to reduce the distance between the free radicals generated by catalysis and the target pollutants, thereby effectively improving the material's degradation performance against resistance genes.

[0116] like Figure 4 As shown, by comparing the infrared spectrum test results of multi-walled carbon nanotubes before and after enhanced carboxylation, it can be seen that the modified multi-walled carbon nanotubes used in Example 1 have obvious absorption peaks at two wavelengths of 1720.19cm-1 and 1573.63cm-1, which are the stretching vibration peaks of the carbon-oxygen double bond (C=O), and an absorption peak is also generated at a wavelength of 1218.79cm-1, which is the stretching vibration peak generated by the carbon-oxygen single bond (CO). The characteristic peaks of the original carbon nanotubes in Comparative Example 2 are not obvious at these locations. Comprehensive analysis shows that through the enhanced carboxylation treatment in this step, I introduced more carboxyl groups on the surface of the original multi-walled carbon nanotubes, providing more active sites for the subsequent introduction of double bonds.

[0117] Comparing Comparative Example 2 with Comparative Example 3, it can be found that after the double bond reaction is introduced, a strong absorption peak is generated at a wavelength of 1643.05 cm-1, representing the stretching vibration of the carbon-carbon double bond (C=C), proving that the double bond structure is successfully loaded on the surface of the modified multi-walled carbon nanotube. The product of cobalt loading by the solvothermal method has the stretching vibration absorption peaks of the Co-O bond in Co3O4 at 663.39 cm-1 and 563.11 cm-1, indicating that Co3O4 has been successfully loaded on the surface of the carbon nanotube. The material with a molecular imprinting structure synthesized by polymerization reaction has a wavelength of 1727.90 cm-1. -1 and 1257.36cm -1 、1157.08cm -1Strong peaks are generated at , which are characteristic peaks respectively generated by the carbon-oxygen double bond (C=O) and carbon-oxygen single bond (CO) contained in the ester group of the polymerization reaction cross-linking agent ethylene glycol dimethacrylate (EGDMA).

[0118] 2. Comparison of Degradation Effects

[0119] Ⅰ. Take the following resistance gene NDM-1 as an example for degradation:

[0120] The acquisition process of the resistance gene NDM-1 is as follows:

[0121] DNA Isolation and Extraction

[0122] In the study of material catalytic advanced oxidation performance, the engineered plasmid pET-29a(+) carrying the resistance gene blaNDM-1 was used as the target ARGs. Fig. 9 The gene map of plasmid pET-29a(+) is shown, in which blaNDM-1 (red part) is 813 bp long and the total length of the plasmid is 6255 bp.

[0123] Bacterial culture

[0124] Prepare 100 mL of LB liquid culture medium (containing 1000 mg of NaCl, 500 mg of yeast powder and 1000 mg of peptone; adjust pH to 7.0-7.2 with NaOH solution), take 200 μl of purified Escherichia coli containing blaNDM-1 resistance gene and add it to the liquid culture medium, then add 100 μl of 30 mg / mL kanamycin, and shake in a constant temperature air bath at 37°C for 12 h to obtain Escherichia coli culture solution.

[0125] Plasmid extraction

[0126] Pipette 1.5 ml of culture solution into a 2 ml centrifuge tube, centrifuge for 30 seconds at 12000 r / min on a tabletop high-speed centrifuge, discard the supernatant, add 1.5 ml of culture solution and repeat the above centrifugation operation twice to enrich the bacteria. Use the plasmid mini-extraction kit (TIANpure Midi Plasmid Kit) to separate and extract the plasmid containing the gene blaNDM-1.

[0127] ARG abundance determination and standard curve drawing The abundance of the resistance gene NDM-1 in the system was quantitatively analyzed by fluorescence quantitative PCR (qPCR). The qPCR Master Mix quantitative PCR kit is used to prepare 20 μL of the reaction system required for qPCR detection. The reaction system is shown in Table 1.

[0128] Table 1 qPCR reaction system

[0129]

[0130] The extracted high-concentration plasmid was used as a standard sample and diluted 5 times in a 10-fold gradient to draw a standard curve. The concentration was detected using a UV-visible spectrophotometer (NanoDrop 8000).

[0131] The DNA copy number was calculated according to the following formula;

[0132]

[0133] The primer information and quantitative PCR conditions of NDM-1 are shown in Table 2. 40 amplification cycles (95°C, 15 min→62°C, 30 s) were performed, and each sample was measured in parallel 3 times. The sample amplification efficiency was 90% to 110%, ensuring the R of the standard curve. 2 >0.99. In the following adsorption degradation experiment, the determination of the abundance of the sample resistance gene was the same as that of the standard curve.

[0134] Table 2 Primer information and quantitative PCR conditions

[0135]

[0136] The logarithm of the resistance gene copy number of the standard sample (lgC) is used as the horizontal axis, and the Ct value measured by qPCR is used as the vertical axis to draw a standard curve, such as Fig.10 The R of the standard curve is shown as 2 >0.99, obtained by standard curve formula The Ct value of the unknown sample was used to quantify the sample in the experiment and calculate the copy number (copies / L).

[0137] II. The catalyst is used in a degradation process of resistance genes in water, and the catalyst is used to catalyze the degradation process; the degradation process is a persulfate advanced oxidation degradation method.

[0138] 1. Degradation test:

[0139] The NDM-1 plasmid extracted from the experiment was used to simulate the antibiotic resistance gene, and all degradation experiments were carried out at room temperature (25°C), in the dark and under sterile conditions; the removal rate was calculated using the following formula;

[0140]

[0141] Where: C t is the absolute abundance of eARG in the system at time t; C0 is the absolute abundance of eARG in the blank sample without the catalytic system (catalyst and PDS).

[0142] Degradation effects of different materials

[0143] Prepare 1mM PDS solution and 2mM Na2S2O3 solution, add 5mL1mM PDS to a 10mL centrifuge tube, add 5μL extracted resistance genes, quickly vortex mix and take out 20μL for the initial resistance gene abundance determination. Then add 5mg MIP catalytic material and NIP catalytic material to the system respectively, place the centrifuge tube in an ultrasonic water bath at 25℃, then take 20μL of the reaction solution and add it to a 2mL centrifuge tube at 1min, 5min, 10min, 20min, and 30min, immediately add 20μL2 mM Na2S2O3 solution to stop the reaction, and then dilute the system to 400μL for resistance gene abundance determination.

[0144] 2. Degradation effect of different resistance gene DNA concentrations:

[0145] Add 5 mL of 2 mM PDS to a 10 mL centrifuge tube, and add 50 μL, 10 μL, 5 μL, and 1 μL of the extracted resistance genes respectively. After quick vortex mixing, take out 10 μL for the initial resistance gene abundance determination; add 5 mg of MIP catalytic material to the system respectively, place the centrifuge tube in an ultrasonic water bath at 25°C, then take 10 μL of the reaction solution into a 2 mL centrifuge tube at 1 min, 5 min, 10 min, 20 min, and 30 min, and immediately add 10 μL of 4 mM Na2S2O3 solution to stop the reaction, and then dilute the system to 400 μL for resistance gene abundance determination.

[0146] 3. The impact of competing pollutants on degradation effects;

[0147] 2mL competitive pollutant degradation reaction systems containing 10mg / L, 20mg / L, and 50mg / L amino acids (acid hydrolyzed casein), humic acid, glucose, and sulfate were prepared in 5mL centrifuge tubes, and each reaction system contained 2mM PDS. Then, 10μL of the extracted resistance gene plasmid was added to the system, and 10μL was taken out for the initial resistance gene abundance determination after rapid vortex mixing. Then, 2mg of molecular imprinting catalytic material was added to each system, and the reaction system was placed in an ultrasonic water bath at 25℃ and oscillated for 30min in the dark. After that, 10μL of the reaction solution was taken out and added to a 2mL centrifuge tube, and 10μL of 4mM Na2S2O3 solution was added to stop the reaction, and then the system was diluted to 400μL for resistance gene abundance determination. At the same time, the degradation efficiency in the absence of competitive pollutants was determined, and the effect of the presence of competitive pollutants on the efficiency of resistance gene degradation was compared.

[0148] 4. Cyclic degradation test

[0149] Take 4 mg of molecularly imprinted catalytic material and put it into a 5 mL centrifuge tube. Take another 5 mL centrifuge tube and add 4 mL of 2 mM PDS, add 40 μL of extracted resistance gene plasmid, and take out 10 μL of reaction solution after rapid vortex oscillation for the initial resistance gene abundance determination. Then add 4 mL of PDS solution containing resistance gene into a 5 mL centrifuge tube containing 4 mg of molecularly imprinted catalytic material, place the centrifuge tube in an ultrasonic water bath at 25 ° C, take 10 μL of reaction solution from the system and add it to a 2 mL centrifuge tube at 5 min, 10 min, 20 min, and 30 min, respectively, and immediately add 10 μL of 4 mM Na2S2O3 solution to stop the reaction, and then dilute the system to 400 μL for resistance gene abundance determination. After the first cycle, place the 5mL centrifuge tube in a centrifuge and centrifuge at 9000r / min for 5 minutes. Discard the liquid in the system, place the separated catalytic material in an 80°C drying oven for drying, and then repeat the above cycle. Calculate the degradation efficiency of each time period in each cycle and draw a curve of the material's cyclic degradation.

[0150] The results are as follows:

[0151] 1. Comparison of the degradation effects of Example 1 and Comparative Example 1;

[0152] The removal effects of the molecular imprinting material of Example 1 and the non-imprinting material of Comparative Example 1 on the catalytic PDS degradation resistance gene are as follows: Figure 5 (a) is shown. The initial concentration of persulfate used in the degradation was 1mM, and the catalyst dosage was 1mg / mL. After 30min of degradation experiment, the removal rate of resistance genes in the system with MIP material as catalyst was 76.08%, while the removal rate of resistance genes in the system with NIP material as catalyst was 61.61%.

[0153] Comparing the catalytic degradation performance of the two materials, the degradation efficiency of the catalytic material containing molecular imprinting is higher. Figure 5 (b) It can be seen that the first-order reaction kinetic constant of the system with MIP material as catalyst is 0.04312min-1, which is significantly larger than the kinetic constant of the system with NIP material as catalyst, 0.02678min-1.

[0154] According to the above experimental results, it can be seen that the catalyst introduced with molecular imprinting can achieve more effective degradation of resistance genes in the persulfate advanced oxidation system compared with the non-imprinted catalyst.

[0155] 2. Degradation effect of different resistance gene DNA concentrations:

[0156] The initial PDS concentration of the system was 2mM, and the catalyst dosage was 1mg / mL. The extracted plasmid was diluted at different times, and the degradation process was as follows Figure 6As shown in (a), for 10.10μg / mL of plasmid, the catalytic degradation efficiency reached 86.39%, and the degradation efficiencies of plasmid concentrations of 3.21μg / mL, 2.01μg / mL and 0.61μg / mL were 81.46%, 80.86% and 80.08%, respectively. The analysis showed that the synthesized molecular imprinting material not only had a good degradation efficiency in the presence of a higher concentration of resistance genes, but also had a high degradation efficiency in the simulation system of low resistance genes. Figure 6 (b) It can be seen that with the increase of DNA concentration, the first-order reaction kinetic constant increased from 0.05388min-1 to 0.06237min-1, and the degradation rate of the resistant gene by the catalytic system gradually increased. This is mainly due to the increase of DNA concentration, which makes it easier for the free radicals generated by persulfate to contact the target pollutants to be degraded.

[0157] 3. Targeted effect:

[0158] The influence of competitive pollutants on degradation effect: Since there are many soluble pollutants in the actual environmental water samples, the experiment explored the influence of different concentrations of competitive pollutants on the degradation efficiency of resistance genes. Figure 7 As shown in the figure, four competitive pollutant systems containing 50 mg / L, 20 mg / L and 10 mg / L were configured, in which amino acids were derived from acid hydrolyzed casein. By comparing the system without adding competitive pollutants, the degradation efficiency of the system with added competitive pollutants was reduced to varying degrees. Among them, 50 mg / L humic acid had the greatest impact on the degradation of resistance genes, and the degradation rate was reduced by 22.38%. The degradation efficiency of the amino acid system decreased by an average of 12.10%, the degradation efficiency of the glucose system decreased by an average of 7.80%, the degradation efficiency of the humic acid system decreased by an average of 11.43%, and the degradation efficiency of the sulfate system decreased by an average of 10.81%. For organic matter such as amino acids, humic acid and glucose, the free radicals generated by the advanced oxidation process cannot show the specificity of the degradation process. Due to the extremely strong oxidation activity of free radicals, the organic pollutants present in the system are easily oxidized and degraded by the free radical process, thereby affecting the degradation efficiency of resistance genes. At the same time, since the molecular imprinting polymer carried by the material is used to identify the structure of hydrogen bonds, and the several competing pollutants containing carboxyl and hydroxyl groups used in the experiment also have chemical structures that can form hydrogen bonds, they will affect the degradation process of resistance genes.

[0159] 4. Cyclic degradation test

[0160] In order to explore the reusability and stability of the loaded guanine molecular imprinted and cobalt oxide catalyst, the performance of the material was determined through multiple cycles of degradation. Figure 8As shown, the degradation efficiency did not decrease with the increase of cycle number, and was basically stable between 75% and 80%, indicating that the material has good repeatability and stability.

Claims

1. A catalyst for selectively catalyzing the degradation of resistance genes in water, characterized in that: The catalyst is a multi-walled carbon nanotube loaded with cobalt tetraoxide and molecular imprinting polymer; the molecular imprinting polymer is used for selectively identifying resistance genes from chemical pollutants in water; the resistance gene is an antibiotic resistance gene produced by pathogenic bacteria.

2. The method for preparing a catalyst for selectively catalyzing the degradation of resistance genes in water according to claim 1, characterized in that: include: S1. Using Co(NO3)2·6H2O as a cobalt source, the cobalt source is loaded onto multi-walled carbon nanotubes by a solvothermal method to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide; the cobalt tetroxide is in the form of nano-microspheres; S2. Adding the multi-walled carbon nanotubes loaded with cobalt tetroxide to a prepolymer formed by a prepolymerization reaction using guanine as a template molecule and methacrylic acid as a functional monomer to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and the prepolymer, and then eluting the template molecules in the multi-walled carbon nanotubes loaded with cobalt tetroxide and the prepolymer to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and a molecular imprinting polymer.

3. The method for preparing a catalyst for selectively catalyzing the degradation of resistance genes in water according to claim 2, characterized in that: Before the step S1, the multi-walled carbon nanotubes are pretreated, wherein the pretreatment method is: performing enhanced carboxylation treatment and vinyl modification treatment on the multi-walled carbon nanotubes in sequence.

4. The method for preparing a catalyst for selectively catalyzing the degradation of resistance genes in water according to claim 3, characterized in that: The enhanced carboxylation treatment of the multi-walled carbon nanotubes comprises: S01, taking equal masses of multi-walled carbon nanotubes and KNO3 and mixing them in a first container, adding water and dispersing them in a ratio of 100 mg of multi-walled carbon nanotubes to water in the range of 10 to 15 mL, and adding concentrated sulfuric acid and dispersing them in a ratio of 100 mg of multi-walled carbon nanotubes to concentrated sulfuric acid in the range of 40 to 50 mL; S02, then add KMnO4 at a mass ratio of multi-walled carbon nanotubes to KMnO4 of 1:2, and place the first container in a 40-50°C water bath for ultrasonic treatment for 2-3h; S03. Raise the water bath temperature to 60-70° C., then add 30% hydrogen peroxide solution at a ratio of 100 mg of multi-walled carbon nanotubes to 15-22 mL of hydrogen peroxide solution, stir and condense under reflux for 35-40 minutes, then lower the temperature to room temperature, add water 5-7 times the volume of the hydrogen peroxide solution to dilute, then filter and wash, complete the enhanced carboxylation treatment of the multi-walled carbon nanotubes, and obtain carboxylated carbon nanotubes.

5. The method for preparing a catalyst for selectively catalyzing the degradation of resistance genes in water according to claim 3, characterized in that: The vinyl modification treatment of the multi-walled carbon nanotubes comprises: S04, in a second container, ultrasonically disperse the carboxylated carbon nanotubes obtained in S03 in SOCl2 liquid at a ratio of 100 mg: 25-30 mL for 25-35 min, then place the second container in a constant temperature water bath at 65-75° C., stir and condense and reflux for 22-26 h, centrifuge, and wash with tetrahydrofuran to obtain a dispersed product; S05. In a third container, the dispersed product is placed in tetrahydrofuran at a ratio of 100 mg: 25-30 mL, and then 4-dimethylaminopyridine and 3-butene-1-ol are added in a ratio of 100 mg: 200-300 mg: 1-2 ml in sequence; then the third container is placed in a constant temperature water bath at 65-75°C, stirred and condensed under reflux for 22-26 hours, centrifuged, washed with tetrahydrofuran, and dried to obtain vinyl-modified multi-walled carbon nanotubes.

6. The method for preparing a catalyst for selectively catalyzing the degradation of resistance genes in water according to claim 2, characterized in that: The method of using a solvothermal method to load a cobalt source onto the surface of a multi-walled carbon nanotube comprises: In a fourth container, dissolve Co(NO3)2·6H2O in n-hexanol at a ratio of 10 mg:1 ml to form a cobalt solution; The mass ratio of multi-walled carbon nanotubes to Co(NO3)2·6H2O is 1 mg:5 mg. The multi-walled carbon nanotubes are placed in a cobalt solution for ultrasonic dispersion for 1 to 3 hours, and then a fourth container is placed in an oil bath at 120 to 180°C, stirred for reaction and condensed under reflux for 8 to 12 hours, cooled to room temperature, and then centrifuged to obtain a black powder. After washing and drying, multi-walled carbon nanotubes loaded with nano-microspherical cobalt tetroxide are obtained.

7. The method for preparing a catalyst for selectively catalyzing the degradation of resistance genes in water according to claim 2, characterized in that: The step of adding the multi-walled carbon nanotubes loaded with cobalt tetroxide to a prepolymer formed by a prepolymerization reaction using guanine as a template molecule and methacrylic acid as a functional monomer comprises: 1) placing the cobalt oxide-loaded multi-walled carbon nanotubes prepared from 100 mg of the multi-walled carbon nanotubes in a fifth container, wherein the fifth container contains a mixed solvent formed by mixing 100 ml of acetonitrile and 20 ml of toluene; 2) Add guanine solution and methacrylic acid into the fifth container, ultrasonicate the fifth container in a water bath at 30-40°C for 30-40 minutes, and then purge with nitrogen for 8-12 minutes; The volume ratio of guanine solution to toluene is 1:1.1-1.5, the guanine solution is an N,N'-dimethylformamide solution with a concentration of 19-23 mol / L guanine, and the molar ratio of guanine to methacrylic acid is 1:5; 3) Then, 6 mmol of a cross-linking agent and 100 mg of an initiator were added to the fifth container, and magnetic stirring was performed for 20 min under N2 conditions; then, the fifth container was placed in a constant temperature water bath at 65-75° C., stirred and condensed under reflux for 10-13 h, and centrifuged to obtain multi-walled carbon nanotubes loaded with cobalt tetroxide and guanine template molecular polymers.

8. The method for preparing a catalyst for selectively catalyzing the degradation of resistance genes in water according to claim 2, characterized in that: The elution of the guanine template molecule includes: sequentially using an eluent consisting of methanol and acetic acid and an HCl solution for elution, and eluting until the supernatant of the re-cleaning solution does not contain guanine, and the elution is completed.

9. A catalyst for selectively catalyzing the degradation of resistance genes in water as claimed in claim 1, characterized in that: The degradation method is a persulfate advanced oxidation degradation method.